Emotion management as struggle in dirty work: the experiences of exotic dancers. (1st January 2014) - Grandy, Gina; Mavin, Sharon
We further the research to date on ambiguity, ambivalence and contradiction in organisation studies by integrating the dirty work and emotion management literatures. Our intent is to better understand the complex cognitive processes underpinning everyday experiences of those working in what has been perceived to be a high-breadth high-depth stigmatised occupation, that is, exotic dancing. Dancers' stories reveal they are acutely aware of social and moral taint associated with the work and in turn their self-identities. They adopt a number of strategies to manage their spoiled identities and we contribute by unpicking the cognitive processes that underpin these strategies. In extending strategies of emotional ambivalence at work and stigma management, we conclude that through a lens of emotion management as struggle, exotic dancers and more broadly dirty workers, do not 'resolve' the ambivalence, contradiction and ambiguity they confront but can be seen to experience at best a type of contingent coherence in their everyday work.